Handling Illegal Levy at Yos Sudarso Port Ambon - Zainuddin, Zainuddin; Hehanussa, Deassy Jacomina Anthoneta; Adam, Sherly (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: The widespread practice of extortion penetrates various areas of life in providing services, one of which is extortion in the fields of transportation, shipping and trade at the Yos Sudarso Ambon port in terms of loading and unloading (stevedore, longshoreman, dockworker) where the shipping company (Tanto, Temas, Meratus and Spil) do not have the right or authority to collect the stupping/stripping (loading and unloading) fees paid by JPT or PBM, however, the bill for the stupping/stripping fees is still collected by the shipping company to this day.Purposes of the Research: Analyze and formulate the penalties for illegal levies that are not based on law. Analyze and discuss efforts to handle illegal levies at Yos Sudarso Port, Ambon.Methods of the Research: Empirical research with the Yos Sudarso Ambon port research location.Results Main Findings of the Research: Levies that are not based on legal regulations are criminal acts as regulated in article 423 of the Criminal Code and article 12 letter e of the Corruption Eradication Law and constitute behavior or acts against the law, exceeding authority, using authority for purposes other than those for which the authority is intended. as regulated in Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. Handling efforts that can be carried out through several stages are that the government needs to provide clear boundaries regarding the position of illegal levies as a qualification for criminal acts as a law enforcement step and criminalize illegal levies as a criminal act of corruption as mandated by UNCAC 2003 which has been ratified based on Law Number 7 In 2006, it became the basis for efforts to handle illegal levies at Yos Sudarso Ambon port.